Quality of life among lung cancer patients undergoing treatment at a tertiary cancer institute in North India - Barwal, Vijay Kumar; Mazta, Salig Ram; Thakur, Anita; Seam, Rajeev Kumar; Gupta, Manish (International Journal of Research in Medical Sciences, 2016)
Background: Lung cancer patients mostly present with advanced disease. Its treatment has shown limited progress in recent decades, so we studied their quality of life (QOL) and how it is affected during treatment. Methods: Patients ≥18 years of age, diagnosed/registered at our institute from 1st September 2012 through August 2013 were included in the study. QOL was assessed by means of the EORTC QLQ-C30 and QLQ-LC13. Data was analyzed using descriptive and inferential statistics Results: Out of 91 patients included in the study, 73 (80.2%) were males and 18 (19.8%) were females. Mean age of the study population was 59.24±10.53 years and median age was 60 years. A better QOL for nausea and vomiting (P=0.011), sleep disturbance (p=0.021), and coughing (p=0.016) was observed in female patients. There was significant worsening in symptom scales of fatigue (p=0.000), nausea and vomiting (p=0.000), sleep (0.006), appetite (p=0.000) and constipation (p=0.000). Though the mean scores of pain, dyspnoea and financial difficulties decreased, but they were not significant. According to the LC13 module, significant improvement was seen in the symptom scales of cough (p=0.000), haemoptysis (p=0.000) and pain chest (p=0.040). Conclusions: Lung cancer patients undergoing treatment suffer many limitations due to an array of symptoms and disruptions in various areas of QOL, arising from both the disease process and its treatment. It should be studied at every visit for each individual patient.